2018
DOI: 10.1016/s0140-6736(18)31719-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloons for small coronary artery disease (BASKET-SMALL 2): an open-label randomised non-inferiority trial

Abstract: Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung, Basel Cardiovascular Research Foundation, and B Braun Medical AG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
232
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(242 citation statements)
references
References 32 publications
5
232
2
3
Order By: Relevance
“…Three RCTs to date have assessed the efficacy and safety of DCB versus DES for de novo small‐vessel CAD . The PICCOLETO study compared the effect of a paclitaxel‐eluting balloon (DIOR; Eurocor, Bonn, Germany) with a first‐generation paclitaxel‐eluting stent (Taxus Liberte, Boston Scientific Corporation, Natick, Massachusetts) and was prematurely stopped due to the increase in the primary angiographic endpoint (% diameter stenosis) and the clinical endpoint in the DCB group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three RCTs to date have assessed the efficacy and safety of DCB versus DES for de novo small‐vessel CAD . The PICCOLETO study compared the effect of a paclitaxel‐eluting balloon (DIOR; Eurocor, Bonn, Germany) with a first‐generation paclitaxel‐eluting stent (Taxus Liberte, Boston Scientific Corporation, Natick, Massachusetts) and was prematurely stopped due to the increase in the primary angiographic endpoint (% diameter stenosis) and the clinical endpoint in the DCB group.…”
Section: Discussionmentioning
confidence: 99%
“…The MACEs rate was similar in both groups after 6 and 24 months, which was in accordance with the similar rate of primary angiographic endpoint (non‐inferiority of in‐stent or in‐balloon late loss) after 6 months. The BASKET‐SMALL2 study was designed to test the clinical noninferiority of a DCB (SeQuent Please, B. Braun Melsungen AG, Melsungen, Germany) to a DES (Taxus element, Boston Scientific Corporation, Natick, Massachusetts, XIENCE, Abbott Vascular, Santa Clara, California, or Promus, Boston Scientific Corporation, Natick, Massachusetts) in a large all‐comers population of 758 patients undergoing PCI of small coronary vessels (reference diameter <3 mm). After 12 months, the MACE rate was similar in both groups of the full‐analysis population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that BMS in combination with DCBs are superior to BMS alone . However, the studies comparing the use of DCB alone versus other strategies (i.e., BA, or DES) in de novo SVD are limited . We conducted a systematic review and meta‐analysis to compare the outcomes of DCB‐only strategy with other modalities in the treatment of de novo coronary SVD.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of restenosis caused by neointimal hyperplasia that frequently lowers the mid- and long-term results of ICAD treatment is well recognized. Angioplasty with a drug-coated balloon (DCB) is already well established and frequently used in cardiology, with DCB-PTA recently demonstrating non-inferiority to the current standard DES-PTA 10. Antiproliferative agents, such as the highly lipophilic microtubular stabilizer paclitaxel, prevent neointimal hyperplasia by inhibiting migration and cell division (figure 1).…”
Section: Introductionmentioning
confidence: 99%